Innovative and sustainable business strategies: The case of portuguese SMEs - Lopes, João M. (2022)
The definition and implementation by Small and Medium Enterprises (SMEs) of innovative and sustainable strategies have increased over time as a solution to obtain a competitive advantage over competitors and to generate positive socio-environmental externalities. This study aims to assess the potential impact of innovative and sustainable strategic management on the performance of Portuguese SMEs. We use a qualitative methodology based on multiple case studies of companies collected through interviews. Although Portuguese SMEs have already adopted some innovative and sustainable strategies, these are integrated into their business models through incremental and defensive innovation strategies and accommodative sustainable strategies, not involving stakeholders to generate greater benefits for all. Many of these strategies are implemented by law enforcement to keep up with competing companies. This study is original because it is based on a case study of multiple companies and contributes to the literature on innovative and sustainable business strategies in SMEs. It is recommended that companies consider, in their strategic plan, innovation and sustainability strategies that allow them to improve their economic performance but also that include the participation of their stakeholders, generating benefits for all.